2013
DOI: 10.1111/brv.12023
|View full text |Cite
|
Sign up to set email alerts
|

Snails and their trails: the multiple functions of trail‐following in gastropods

Abstract: Snails are highly unusual among multicellular animals in that they move on a layer of costly mucus, leaving behind a trail that can be followed and utilized for various purposes by themselves or by other animals. Here we review more than 40 years of experimental and theoretical research to try to understand the ecological and evolutionary rationales for trail-following in gastropods. Data from over 30 genera are currently available, representing a broad taxonomic range living in both aquatic and terrestrial en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 185 publications
(348 reference statements)
3
101
0
Order By: Relevance
“…The ability to detect and follow chemical trails left by the prey is demonstrated for the first time in a species of Geoplaninae. Such a behaviour was already observed in species of other subfamilies of land planarians such as Bipaliinae and Rhynchodeminae, using similar experiments (Fiore et al 2004;Winsor et al 2004;Iwai et al 2010), as well as in other predators of land gastropods, such as the predatory snail Euglandina rosea (Férrussac) and carabid beetles (Parakinen 1994;Holland et al 2012;Ng et al 2013). The presence of sensorial pits in the anterior region of the body of land planarians (Dendy 1891;Carbayo 2010) may be related to this ability to detect chemical trails.…”
Section: Discussionsupporting
confidence: 61%
“…The ability to detect and follow chemical trails left by the prey is demonstrated for the first time in a species of Geoplaninae. Such a behaviour was already observed in species of other subfamilies of land planarians such as Bipaliinae and Rhynchodeminae, using similar experiments (Fiore et al 2004;Winsor et al 2004;Iwai et al 2010), as well as in other predators of land gastropods, such as the predatory snail Euglandina rosea (Férrussac) and carabid beetles (Parakinen 1994;Holland et al 2012;Ng et al 2013). The presence of sensorial pits in the anterior region of the body of land planarians (Dendy 1891;Carbayo 2010) may be related to this ability to detect chemical trails.…”
Section: Discussionsupporting
confidence: 61%
“…There are some strategies of snails to find attractive food patches. B. tentaculata selects for food quality (Brendelberger, 1997) and studies by Moelzner and Fink (2014) indicated that odours of biofilm food organisms may aid Lymnaea stagnalis in finding attractive biofilms and Ng et al (2013) showed that snails follow the mucus trails of other snails, a behavioural strategy that also may help to find attractive food patches.…”
Section: Attractiveness Of Biofilms For Snailsmentioning
confidence: 99%
“…Attractin, Temptin, Enticin and Seductin are small molecules that act as water-borne sex pheromones promoting mate attraction (Painter et al, 1998(Painter et al, , 2004Cummins et al, 2004). These pheromones were first described in the marine mollusc Aplysia (sea slug/sea hare), and in terrestrial snails where they are implicated in trail-following (Ng et al, 2013). The expression of Attractin and Temptin has been detected in the transcriptomes of earthworm tissues, including epidermis and digestive tract (Novo et al, 2013), forming physical and functional interfaces with the environment, thus suggesting that the behaviour-modulating molecules could be released through the mucus or faeces ("casts") to create a trail (Ressler et al, 1968) analogous to those in snails for the attraction of potential mates.…”
Section: Introductionmentioning
confidence: 99%